Auctioning of EU ETS Phase II Allowances: How and Why? - Hepburn, C; Grubb, M; Neuhoff, K; Matthes, F; Tse, M (2006)
The European Directive on the EU ETS allows governments to auction up to 10% of the allowances issued in phase II 2008-2012, without constraints being specified thereafter. This article reviews and extends the long-standing debate about auctioning, in which economists have generally supported and industries opposed a greater use of auctioning. The article clarifies the key issues by reviewing six 'traditional' considerations, examines several credible options for auction design, and then proposes some new issues relevant to auctioning. It is concluded that greater auctioning in aggregate need not increase adverse competitiveness impacts, and could in some respects alleviate them, particularly by supporting border-tax adjustments. Auctioning within the 10% limit might also be used to dampen price volatility during 2008-2012 and, in subsequent periods, it offers the prospect of supporting a long-term price signal to aid investor confidence. The former is only possible, however, if Member States are willing to coordinate their decision-making (though not revenue-raising) powers in defining and implementing the intended pricing mechanisms.